2022
DOI: 10.3390/pharmaceutics14091891
|View full text |Cite
|
Sign up to set email alerts
|

Mitotane Nanocarriers for the Treatment of Adrenocortical Carcinoma: Evaluation of Albumin-Stabilized Nanoparticles and Liposomes in a Preclinical In Vitro Study with 3D Spheroids

Abstract: Adrenocortical carcinoma (ACC) is a heterogeneous malignancy related to poor prognosis and limited treatment options. The orphan drug mitotane (MT) is still a cornerstone in ACC therapy, however, its application is characterized by low aqueous solubility, poor bioavailability, and unfavorable pharmacokinetics, often resulting in below-target plasma concentrations or toxic side effects. Throughout the last decades, nanoparticulate formulations have become attractive carriers to improve anticancer therapy. In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…In addition, the low number of H295R cells present in the Adrenoids probably does not allow to measure cortisol, which was detectable only when a 10 3 -fold higher number of H295R were grown in monolayer conditions. To date, several attempts have been performed to induce homo-cell spheroids from H295R cells with different methods with variable efficacy [30][31][32][33][34][35] , showing different cell viability and growth rate. In our hands, homotypic www.nature.com/scientificreports/ spheroids obtained by H295R cells were not able to either compact properly and maintain steroidogenic activity, as shown in the Supplemental Data.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the low number of H295R cells present in the Adrenoids probably does not allow to measure cortisol, which was detectable only when a 10 3 -fold higher number of H295R were grown in monolayer conditions. To date, several attempts have been performed to induce homo-cell spheroids from H295R cells with different methods with variable efficacy [30][31][32][33][34][35] , showing different cell viability and growth rate. In our hands, homotypic www.nature.com/scientificreports/ spheroids obtained by H295R cells were not able to either compact properly and maintain steroidogenic activity, as shown in the Supplemental Data.…”
Section: Discussionmentioning
confidence: 99%
“…Indirect quantification of adsorbed protein was performed through UV–Vis spectroscopy on a Shimadzu 1900i apparatus, using a modified Bradford assay. 40 In brief, aliquots from the supernatant from the first centrifugation (20 μL) were incubated with 1.8 mL of protein assay dye for at least 15 min and absorbance was read at 595 nm. Calibration curve was linear in the range of 0–800 μg/mL BSA ( R 2 = 0.993).…”
Section: Methodsmentioning
confidence: 99%
“…Recently, two interesting studies addressed the main challenges regarding the ACC standard-of-care drug mitotane by implementing NCI-H295R spheroids. The authors aimed to overcome the well-known poor bioavailability and unfavorable pharmacokinetics of this drug by the successful development of three potentially injectable nanoparticle formulations: a micellar [ 97 ], a liposomal and an albumin-bound variant [ 98 ]. The newly developed albumin-stabilized formulation not only displayed increased cytotoxic properties, but furthermore caused the disintegration of the spheroids, which was not detectable for the parental drug [ 98 ].…”
Section: Adrenalmentioning
confidence: 99%
“…The authors aimed to overcome the well-known poor bioavailability and unfavorable pharmacokinetics of this drug by the successful development of three potentially injectable nanoparticle formulations: a micellar [ 97 ], a liposomal and an albumin-bound variant [ 98 ]. The newly developed albumin-stabilized formulation not only displayed increased cytotoxic properties, but furthermore caused the disintegration of the spheroids, which was not detectable for the parental drug [ 98 ]. Interestingly, Avena et al demonstrated that XCT790, an inverse agonist for estrogen receptor α, was able to reduce 3D spheroid formation and motility not only in H295R cells, but also in the mitotane-resistant MUC-1 model, suggesting that such an approach could be another effective option for the treatment of mitotane-resistant ACC [ 99 ].…”
Section: Adrenalmentioning
confidence: 99%